1985
DOI: 10.1021/ac50001a027
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Laser and Ion Microprobe Detection Sensitivity for Lead in Biological Microanalysis

Abstract: Lead detection sensitivity In doped epoxy standards was compared for the Leybold Heraeus LAMMA 500 laser microprobe vs. the Cameca IMS-3f Ion microscope (modified for high sensitivity digital Imaging). For comparable lateral spatial resolutions of about 1 µ , the LAMMA relative detection limit of 5 µ /g Is superior to that of the IMS-3f by more than 2 orders of magnitude. However, the analytical volume of the latter (0.02 µ 3) was only about 0.05 that of LAMMA measurement as the result of differences In analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1989
1989
1996
1996

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Assuming no spectral interferences, a detection limit for Al of c. 1 /ug g~^ (37 nmol g^^) or better can be achieved by SIMS (Linton et al, 1980;Lazof et al, 1994a), a figure which is at least an order of magnitude better than for EDXMA (Chandler, 1979;Linton et al, 1980; but see Marienfeld & Stelzer, 1993, who claimed a detection limit not better than 2-3 //,mol g"^), "Al NMR (Nagata et al, 1991) and LAMMA (Verbueken et al, 1984;Linton et al, 1985), and more than two orders of magnitude better than PIXE (Hult et al, 1992). The latter technique apparently lacks sufficient sensitivity to measure Al in various subcellular structures and is therefore only suitable for gross localization of Al accumulated in root tissues.…”
Section: In Situ Techniques For Measurement Of Aluminiummentioning
confidence: 99%
“…Assuming no spectral interferences, a detection limit for Al of c. 1 /ug g~^ (37 nmol g^^) or better can be achieved by SIMS (Linton et al, 1980;Lazof et al, 1994a), a figure which is at least an order of magnitude better than for EDXMA (Chandler, 1979;Linton et al, 1980; but see Marienfeld & Stelzer, 1993, who claimed a detection limit not better than 2-3 //,mol g"^), "Al NMR (Nagata et al, 1991) and LAMMA (Verbueken et al, 1984;Linton et al, 1985), and more than two orders of magnitude better than PIXE (Hult et al, 1992). The latter technique apparently lacks sufficient sensitivity to measure Al in various subcellular structures and is therefore only suitable for gross localization of Al accumulated in root tissues.…”
Section: In Situ Techniques For Measurement Of Aluminiummentioning
confidence: 99%
“…In some reports, an acceptable agreement with the model's predictions is shown, whereas in others the inapplicability of the approach is stressed and the use of calibration curves is proposed as an alternative (134)(135)(136)(137)(138)(139)(140)(141)(142)(143)(144). A variety of instrumental factors require attention when quantitation is attempted (145).…”
Section: Signal Registrationmentioning
confidence: 99%
“…The comparative use of TOF LMMS and micro-ESCA and AES for the study of oxide layers on stainless steel revealed that LMMS was especially useful because of its higher sensitivity and its capability to detect light elements (162). TOF LMMS was shown to exhibit better detection limits than dynamic SIMS for the analysis of elements in biological materials (47,141).…”
Section: Techniquesmentioning
confidence: 99%